Tinjauan Mendalam Tentang Pentingnya dan Analisis Penggunaan Biaya Berbasis Aktivitas: Perbandingan dengan Pendekatan Konvensional dalam Konteks Pengambilan Keputusan Manajerial - John Peter Naibaho; Rahmat Silaban; Darni Santi Telaumbanua; Hamonangan Siallagan (CV. Ulil Albab Corp, 2024)
Activity-Based Costing (ABC) is a crucial method for companies to allocate resources efficiently and identify areas that need improvement. ABC assigns resource costs to cost objects such as products, services, or customers based on the activities performed for those cost objects. By breaking down costs into specific activities, organizations can gain a deeper understanding of their expenditures and their impact on overall performance. This allows companies to identify inefficient or unnecessary processes, thereby reducing costs and improving operational efficiency. Furthermore, effective cost management is essential for achieving organizational goals, monitoring and controlling expenditures, and integrating new financial performance measures such as Economic Value Added (EVA) and balanced scorecards. Analyzing cost usage based on activities enables companies to identify cost reduction opportunities and process improvements, ultimately leading to enhanced efficiency and long-term profitability. By adopting this approach, companies can ensure that resources are utilized efficiently and effectively to drive growth and sustainability in a competitive market. Implementing ABC helps companies gain a detailed understanding of cost drivers, predict potential challenges and risks, and develop strategies to mitigate negative impacts. Overall, ABC is a vital tool in cost management strategy, aiding companies in achieving competitive advantage and long-term sustainability.